Calculus as a Risk Factor for Periodontal Disease: Narrative Review on Treatment Indications When the Response to Scaling and Root Planing Is Inadequate - Stephen K. Harrel; Charles M. Cobb; Lee N. Sheldon; Michael P. Rethman; John S. Sottosanti (MDPI AG, 2022)
Background: Based on the 2018 classification of periodontal disease, a series of articles have been published describing the decision points of periodontal therapy and how the findings collected at those decision points can be used as guidelines for periodontal therapy. The articles are reviewed with a focus on the finding of inadequate calculus removal at the decision points and how that finding impacts treatment outcomes. Methods: A narrative review of the literature discussing the influence of calculus on inflammation was performed and the effects of inadequate removal of calculus during periodontal therapy were analyzed in light of the 2018 classification of periodontal disease, the decision points of periodontal therapy, and the guidelines of periodontal therapy. Results: The published literature supports that calculus is a major risk factor for periodontal inflammation. Recent studies indicate that the pathologic risk of calculus goes beyond the retention of biofilm and may represent a different pathophysiologic pathway for periodontal disease separate from the direct action of biofilm. The inadequate removal of calculus is a factor in the failure of periodontal therapy. Conclusions: The inadequate removal of calculus plays an important role in the frequent failure of non-surgical periodontal therapy to eliminate inflammation.